\(Jasminum binhchauense\) (Oleaceae), a new species from Binh Chau-Phuoc Buu Nature Reserve in Southern Vietnam - Thi Thanh, Nguyen; Van Son, Le; Hong quang, Bui (Academia Journal of Biology, 2023)
Jasminum binhchauense, a new species of the family Oleaceae, is described and illustrated. The species was collected during 2022–2023 from Binh Chau-Phuoc Buu Nature Reserve, Ba Ria-Vung Tau province, southern Vietnam. The new species differs from its congeners in its branchlets, leaf blade, petioles and calyx. A taxonomic description, a table comparing morphological characters of the allied species, and illustrations, a color photo-plate are provided.